Women’s Expectations and Experiences Regarding Nursing Support during Childbirth - Sabah M. Metwally; Nabaweya S. Shehata; Sabah A. Abd El haleem (Evidence-Based Nursing Research)
Context: Women giving birth always need to be provided by support and care during childbirth, trustful relationships with the health professionals, mainly childbirth nurses. The midwife can promote women feeling of being empowered and subsequently having positive experience and satisfaction during childbirth.